PENDETEKSIAN KECURANGAN LAPORAN KEUANGAN DENGAN ANALISIS FRAUD DIAMOND MENGGUNAKAN MODEL FRAUD SCORE (F-SCORE) PADA PERUSAHAAN BUMN SEKTOR BASIC MATERIAL DAN SEKTOR INFRASTRUKTUR YANG TERDAFTAR DI BEI TAHUN 2019-2023 - Putri, Annisa; Santoso, Budi (Publika Citra Media, 2025)
This study aims to detect the level of risk of fraud in the company's financial statements. The variables used to achieve the research objectives were accrual quality which was proxied with RSST, financial performance proxied by change in receivable, change in inventory, change in cash sales and change in earnings. To detect the risk of financial statement fraud as a dependent variable in this study, the F-Score value is used which is the sum of the variables of discretionary accrual and financial performance. The population of this study is state-owned companies in the Basic Materials & Infrastructure Sector listed on the Indonesia Stock Exchange from 2019 to 2023. In this study, the sample used was as many as 12 state-owned companies in the Basic Materials & Infrastructure Sector listed on the Indonesia Stock Exchange from 2019 to 2023. The type of data used is secondary data in the form of annual financial statements of state-owned companies listed on the Indonesia Stock Exchange from 2019 to 2023. Hypothesis testing was carried out by multiple linear regression methods. The results of this study show that the variables of financial target and external pressure have an effect on financial statement fraud. This study does not prove that financial stability, ineffective monitoring nature of industry, total accrual to total assets, change in auditor and change in director have an influence on financial statement fraud. Therefore, it can be concluded that the variables in fraud diamond can be used in detecting financial statement fraud.